Identification of 6-amino-1H-pyrazolo[3, 4-d]pyrimidines with in vivo efficacy against visceral leishmaniasis. Issue 10 (6th August 2020) - Thomas, Michael G.; De Rycker, Manu; Ajakane, Myriam; Crouch, Sabrinia D.; Campbell, Lorna; Daugan, Alain; Fra, Gloria; Guerrero, César; Mackenzie, Claire J.; MacLean, Lorna; Manthri, Sujatha; Martin, Franck; et al.
Abstract : The development of a chemical series with oral efficacy against visceral leishmaniasis is described. Abstract : Visceral leishmaniasis (VL) affects millions of people across the world, largely in developing nations. It is fatal if left untreated and the current treatments are inadequate. As such, there is an urgent need for new, improved medicines. In this paper, we describe the identification of a 6-amino- N -(piperidin-4-yl)-1 H -pyrazolo[3, 4- d ]pyrimidine scaffold and its optimization to give compounds which showed efficacy when orally dosed in a mouse model of VL.